Trends in bio-behavioural risk factors of non-communicable diseases among adults in Sao Tome and Principe - Pengpid, Supa; Peltzer, Karl (Frontiers in Public Health, 2023)
Background: Understanding national trends in risk factors of noncommunicable diseases (NCDs) may have health policy implications. The aim of the study was to assess the prevalence and social and demographic factors associated with risk factors of NCDs in adults from 2008 to 2019 in Sao Tome and Principe. Methods: In repeat cross-sectional national STEPS surveys 2,457 adults (median age 37 years) in 2008 and 1,893 adults (median age 38 years) in 2019 in Sao Tome and Principe responded to structured interviews, physical and biochemical measures. Logistic regressions were applied to estimate predictors of NCD risk factors. Results: Having three to seven NCD risk factors significantly decreased among men but not women from 36.6% in 2008 to 26.8% in 2019. The proportion of specific risk factors of NCD increased significantly for low physical activity from 17.4% in 2008 to 30.9% in 2019, and overweight/obesity from 37.3% in 2008 to 51.0% in 2019. Insufficient fruit/vegetable consumption decreased from 83.1% in 2008 to 53.3% in 2019, frequent alcohol use from 32.6% in 2008 to 24.8% in 2019, and diabetes from 3.1% in 2008 to 1.2% in 2019, while the proportion of current tobacco use and hypertension remained unchanged from 2008 to 2019.Men engaged more often than women in current tobacco use and frequent alcohol use, and women had higher rates of low physical activity and overweight/obesity than men. Higher educational levels were positively associated with overweight/obesity, and inversely associated with frequent alcohol use and inadequate fruit/vegetable intake.Between 2008 and 2019, the prevalence of seven risk factors for NCDs in Sao Tome and Principe declined among men, but not among women. Several associated variables have been identified for each individual risk factor of NCD that may help guide interventions.